REPAIR OF PROCESS EXTORTION OF CENTRIFUGAL OIL AND ADJUSMENT OF TECHNOLOGY IS PRECISELY UTILIZE AT INDUSTRY CHIPS EMPING GEPUK MELINJO DI KABUPATEN BATANG - Abidin, Zainal (Universitas Diponegoro, 2007)
Abstract At the industry produce the chips emping gepuk melinjo conventional generally experience of the resistance at process extortion of oil because this process walk gravitationly with extortion time about 0.5 hour. Problems of arising out is oil conten in chips emping gepuk melinio still high about 15 % is while equipments of extortion of oil which have is not yet can operate in an optimal fashion ( leak is in gravitation with time of 30 minute). is so that needed by the equipments able to improve ; repair the process extortion of oil in chips emping gepuk melinjo fry. This matter will pursue in improvement of capacities produce the chips emping gepuk melinio. To increase product to be needed modify, equipments of extortion of oil, so that efiensi production can be boasted up and peaceful for the use it and also improve the chips emping product qualitv gepuk. As according to the clauses released by Departemen Kesehatan, oil content in food stuff fried by is less than 5%. because at high oil rate will quicken the process rancidity at food-stuff. Besides with high oil rate will be able to improve the cholesterol rate in blood. From the result of perception during extortion by centrifugal oil wringer, extortion time about 2 - 3 minute with oil content in chips emping gepuk under or less than 5 %, so that the result of chips emping gepuk yielded by seen drier and will improve the endurance. Keyword : Chips emping gepuk melinjo, centrifugal wringer,oil rate and extortion time.